2007
DOI: 10.1016/j.jcrs.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inferior-segment Intacs with and without C3-R on keratoconus

Abstract: The addition of C3-R to the Intacs procedure resulted in greater keratoconus improvements than Intacs insertion alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
3
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(180 citation statements)
references
References 14 publications
4
159
3
11
Order By: Relevance
“…In a case series of Intacs ICRS with 3-year follow-up in 13 eyes, significant increases in average K values were observed between 6 months and 3 years, indicating that disease stabilisation was not achieved by ICRS alone. 51 Combined ICRS and CXL ICRS implantation can be combined with CXL, [52][53][54][55][56] but the treatment sequence is important: ICRS appears more effective in improving corneal shape before the cornea is stiffened with CXL. Coskunseven et al, 52 in an RCT comparing CXL first and ICRS later (group 1) with ICRS first and later CXL (group 2), showed significantly greater improvements (mean 7 months follow-up) in spectacle CDVA (three line gain (group 1); two line gain (group 2), Po0.01) and manifest astigmatism (2.48D mean absolute cylinder reduction (group 1); 1.76D reduction (group 2), Po0.05) where ICRS was performed first.…”
Section: Clinical Pathways For Keratoconus Dm Gore Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In a case series of Intacs ICRS with 3-year follow-up in 13 eyes, significant increases in average K values were observed between 6 months and 3 years, indicating that disease stabilisation was not achieved by ICRS alone. 51 Combined ICRS and CXL ICRS implantation can be combined with CXL, [52][53][54][55][56] but the treatment sequence is important: ICRS appears more effective in improving corneal shape before the cornea is stiffened with CXL. Coskunseven et al, 52 in an RCT comparing CXL first and ICRS later (group 1) with ICRS first and later CXL (group 2), showed significantly greater improvements (mean 7 months follow-up) in spectacle CDVA (three line gain (group 1); two line gain (group 2), Po0.01) and manifest astigmatism (2.48D mean absolute cylinder reduction (group 1); 1.76D reduction (group 2), Po0.05) where ICRS was performed first.…”
Section: Clinical Pathways For Keratoconus Dm Gore Et Almentioning
confidence: 99%
“…[43][44][45][46][52][53][54][55][56] We would therefore argue for gross shape correction with ICRS implantation followed by CXL, fine shape correction with PRK if necessary, then finally pIOL implantation as a logical pathway to visual rehabilitation in grade II-III keratoconus (Figure 4). …”
Section: Refractive Correction-piol Implantationmentioning
confidence: 99%
“…Chan et al demonstrated the effectiveness of riboflavin/UVA induced CXL on patients whose eyes had their epithelium left intact. The eyes were soaked in riboflavin (0.1% riboflavin-5-phosphate and dextran) for 5 min and penetration reached half of the entire corneal depth [177]. The study reported significant success in reducing the severity of keratoconus.…”
Section: Riboflavin-based Bioadhesivementioning
confidence: 99%
“…Chan et al 8 , and mean K after CXL in patients who had already been implanted with Intacs rings, on average 7 months before. The authors have, therefore, suggested that CXL had an additive effect on Intacs implantation and might be considered an enhancement/stabilizing procedure.…”
Section: Collagen Cross-linking and Icrs: Sequential Vs Simultaneous mentioning
confidence: 99%